2011
DOI: 10.1186/1471-2393-11-11
|View full text |Cite
|
Sign up to set email alerts
|

Women-focused development intervention reduces delays in accessing emergency obstetric care in urban slums in Bangladesh: a cross-sectional study

Abstract: BackgroundRecognizing the burden of maternal mortality in urban slums, in 2007 BRAC (formally known as Bangladesh Rural Advancement Committee) has established a woman-focused development intervention, Manoshi (the Bangla abbreviation of mother, neonate and child), in urban slums of Bangladesh. The intervention emphasizes strengthening the continuum of maternal, newborn and child care through community, delivery centre (DC) and timely referral of the obstetric complications to the emergency obstetric care (EmOC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
59
1
4

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(73 citation statements)
references
References 20 publications
9
59
1
4
Order By: Relevance
“…The minimal sample size required for this study was calculated using the Epi Info version 7.02 statistical software package with the assumption of 95% confidence level (Zα/2= 1.96), 80% power (Zβ= 0.84). The magnitude of first, second, and third maternal delays in utilizing institutional delivery service were 37.8%, 14 29.7%, 15 and 34.7% 16 respectively. Considering a 10% nonresponse rate, the maximum sample size requires for this study was found to be 394 postnatal mothers (for first delay), 352 postnatal mothers (second delay), and 383 postnatal mothers (third delay).…”
Section: Sample Size and Sampling Proceduresmentioning
confidence: 95%
“…The minimal sample size required for this study was calculated using the Epi Info version 7.02 statistical software package with the assumption of 95% confidence level (Zα/2= 1.96), 80% power (Zβ= 0.84). The magnitude of first, second, and third maternal delays in utilizing institutional delivery service were 37.8%, 14 29.7%, 15 and 34.7% 16 respectively. Considering a 10% nonresponse rate, the maximum sample size requires for this study was found to be 394 postnatal mothers (for first delay), 352 postnatal mothers (second delay), and 383 postnatal mothers (third delay).…”
Section: Sample Size and Sampling Proceduresmentioning
confidence: 95%
“…Nonetheless, maternal and newborn survival programmes could further stress the importance of a woman's support and care from family members during pregnancy and childbirth; this could be done, for example, through mass media campaigns. Interventions through women's groups and income‐generating activity programmes may also be beneficial 34,35 …”
Section: Commentsmentioning
confidence: 99%
“…Interventions through women's groups and income-generating activity programmes may also be beneficial. 34,35 Conclusion Programmatic efforts are often divided between facility-based and community-based approaches and between maternal and newborn survivals. As a fetus' health is inextricably linked with the mother's health during pregnancy and labour, a more integrated approach to improving a woman's well-beingincluding improving her access to financial and social resources -may be needed to reduce both maternal and fetal mortality.…”
Section: Programme Implicationsmentioning
confidence: 99%
“…8 Salah satu alasan penundaan akses kepelayanan kesehatan adalah karena ketidakmampuan ibu hamil dalam mengenali kondisi kehamilannya. 9 Faktor risiko yang mempengaruhi kejadian perdarahan pascapersalinan pada kehamilan, antara lain placenta previa, atonia uteri, infeksi penyakit, gizi buruk, eklamsia, paritas ibu hamil, anemia kehamilan, jarak persalinan, usia kehamilan, umur ibu, riwayat pemeriksaan kehamilan (ANC), dan riwayat persalinan terdahulu. Faktor risiko yang mempengaruhi terhadap kejadian preeklamsia, antara lain hipertensi, jarak kehamilan, paritas, kehamilan ganda, usia ibu hamil < 20 tahun dan > 35 tahun, genetik, obesitas, infeksi, dan status gizi.…”
Section: Pendahuluanunclassified